Positive electrode material and preparation method thereof, positive electrode plate and sodium ion battery
By adding a carbon-containing coating on the sodium vanadium fluorophosphate positive electrode material and optimizing the preparation conditions, the problem of insufficient capacity and conductivity of the NVPF material is solved, and the energy density and electrochemical performance of the sodium ion battery are significantly improved.
Patent Information
- Application Number
- CN202411499539.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The existing sodium ion battery positive electrode material, vanadium fluorophosphate (NVPF), has problems with poor capacity and poor electronic conductivity, resulting in low energy density of sodium ion batteries.
Using sodium vanadium fluorophosphate (Na3V2(PO4)2F3) with a carbon-containing coating layer as the positive electrode material, the purity and conductivity of the material are improved by controlling the coating rate and carbon element mass fraction, and combined with specific preparation methods and conditions, such as Adjust the pH value and calcination treatment temperature to form a dense carbon-containing coating.
It significantly improves the capacity of the positive electrode material and the energy density of the sodium ion battery, improves the corrosion resistance and electronic conductivity of the material, and ensures efficient electrochemical performance.
Smart Images

Figure CN119324218A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet and a sodium ion battery. Background Art
[0002] Sodium-ion battery (SIB) is another secondary battery with great application prospects after lithium-ion battery (for example, in the field of new energy vehicles). Its electrochemical performance mainly depends on the performance of its positive electrode. Among the various positive electrode materials of sodium-ion batteries, sodium vanadium fluorophosphate (Na3V2(PO4)2F3, NVPF) has a theoretical working voltage of about 3.85V and a theoretical specific capacity of 128.3mAh / g, which is a very promising positive electrode material for sodium-ion batteries. However, the NVPF materials actually prepared at present still have the problem of poor capacity, which makes the energy density of sodium-ion batteries not high; and although the NVPF material itself has good ionic conductivity, its electronic conductivity is poor. Summary of the invention
[0003] In view of the technical problems existing in the background technology, the present application provides a positive electrode material and a preparation method thereof, a positive electrode plate and a sodium ion battery, aiming to solve the technical problems of poor capacity and poor electronic conductivity of the NVPF materials currently prepared.
[0004] In a first aspect, an embodiment of the present application provides a positive electrode material, comprising a core and a carbon-containing coating layer covering at least a portion of the surface of the core, wherein the core comprises sodium vanadium fluorophosphate (Na3V2(PO4)2F3);
[0005] A button battery is prepared by using the positive electrode material, and the button battery is subjected to an Nth charge-discharge test. In the discharge curve of the Nth charge-discharge test, the discharge specific capacity is C0, the discharge specific capacity of the discharge platform corresponding to the voltage of 3.3V to 3.4V is C1, and C1 / C0<6.7%, wherein N is an integer greater than or equal to 1;
[0006] The conditions of the Nth charge-discharge test are: at 20° C. to 30° C., the button battery is charged to 4.3V at a constant current of 0.2C, and then discharged to 2V at a constant current of 0.2C.
[0007] In the technical solution of the embodiment of the present application, C1 / C0 is controlled to be less than 6.7%, indicating that the purity of Na3V2(PO4)2F3 in the core of the positive electrode material is relatively high, while the mass proportion of impurities such as Na3V2(PO4)3 is relatively low, which effectively improves the capacity of the positive electrode material and the energy density of the sodium ion battery. At the same time, the carbon-containing coating layer in the positive electrode material can effectively improve the electronic conductivity of NVPF, so that the capacity of the material can be further improved.
[0008] In some embodiments, at least one of the following conditions is met:
[0009] (1) C1 / C0≤3.5%;
[0010] (2) The coverage rate of the carbon-containing coating layer on the surface of the inner core is 89% to 100%, preferably 95% to 100%;
[0011] (3) The porosity of the positive electrode material is 10% to 69%, preferably 15% to 30%.
[0012] In the technical solution of the embodiment of the present application, the porosity is within the above range, which is conducive to ensuring the entry and exit of sodium ions while making the carbon-containing coating layer have a higher density, which is conducive to improving the compaction density of the positive electrode material. C1 / C0 is within the above range, which can make the purity of the NVPF phase in the positive electrode material higher, and can further effectively improve the capacity of the positive electrode material and the energy density of the sodium ion battery. The coverage rate of the surface of the carbon-containing coating layer coating the inner core is within the above range, which is conducive to improving the capacity and corrosion resistance of the positive electrode material, and can make the positive electrode material have good electronic conductivity.
[0013] In some embodiments, the mass fraction of carbon in the positive electrode material is 1.25% to 6%, preferably 1.5% to 3.5%.
[0014] In the technical solution of the embodiment of the present application, the mass fraction of the carbon element in the positive electrode material is within the above-mentioned range, which can enable the positive electrode material to have a higher compaction density and electronic conductivity; the coverage rate of the surface of the carbon-containing coating layer coating the inner core is within the above-mentioned range, which is beneficial to the improvement of the capacity and corrosion resistance of the positive electrode material, and can enable the positive electrode material to have good electronic conductivity.
[0015] In some embodiments, the cathode material has a compaction density of 1.4 g / cm 3 ~2g / cm 3 , preferably 1.53 g / cm 3 ~1.99g / cm 3 .
[0016] In the technical solution of the embodiment of the present application, the positive electrode material has a higher compaction density, which is beneficial for the sodium ion battery to have a higher energy density.
[0017] In a second aspect, an embodiment of the present application provides a method for preparing a positive electrode material, comprising:
[0018] Providing a mixed slurry, wherein the mixed slurry comprises a sodium source, a fluorine source, a vanadium source, a phosphorus source and a carbon source;
[0019] The mixed slurry is dried to obtain a precursor;
[0020] The precursor is calcined to obtain the positive electrode material;
[0021] The positive electrode material comprises a core and a carbon-containing coating layer covering at least a portion of the surface of the core, wherein the core comprises sodium vanadium fluorophosphate (Na3V2(PO4)2F3); a button battery is made of the positive electrode material, and the button battery is subjected to an Nth charge-discharge test. In the discharge curve of the Nth charge-discharge test, the discharge specific capacity is C0, and the discharge specific capacity of the discharge platform corresponding to the voltage of 3.3V to 3.4V is C1, C1 / C0<6.7%, wherein N is an integer greater than or equal to 1; the conditions of the Nth charge-discharge test are: at 20°C to 30°C, the button battery is charged to 4.3V at a constant current of 0.2C, and then discharged to 2V at a constant current of 0.2C.
[0022] The inner core of the positive electrode material obtained by the above-mentioned preparation method provided by the present application has a high purity of Na3V2(PO4)2F3, while the mass proportion of impurities such as Na3V2(PO4)3 is low, thereby effectively improving the capacity of the positive electrode material and the energy density of the sodium ion battery. At the same time, the carbon-containing coating layer in the positive electrode material obtained by the above-mentioned preparation method can effectively improve the electronic conductivity of NVPF, so that the capacity of the material can be further improved.
[0023] In some embodiments, the carbon source comprises at least one of citric acid, polyvinyl alcohol, glucose, sucrose and oxalic acid, optionally comprises citric acid and / or polyvinyl alcohol, and further optionally comprises citric acid and polyvinyl alcohol;
[0024] Optionally, when the carbon source is citric acid and polyvinyl alcohol, the mass ratio of the citric acid to the polyvinyl alcohol is 2:1 to 1:4;
[0025] Optionally, the polyvinyl alcohol includes at least one of polyvinyl alcohol 2000, polyvinyl alcohol 3000, polyvinyl alcohol 4000 and polyvinyl alcohol 6000.
[0026] In the technical solution of the embodiment of the present application, when the carbon source includes citric acid and polyvinyl alcohol, the compounding of citric acid and polyvinyl alcohol can produce a mutually promoting effect, thereby achieving a further improvement in the compaction density, which is beneficial to improving the energy density of the sodium ion battery using the positive electrode material.
[0027] In some embodiments, at least one of the following conditions is met:
[0028] (1) The sodium source comprises at least one of sodium fluoride, sodium phosphate, sodium bicarbonate and sodium nitrate, and optionally comprises sodium fluoride;
[0029] (2) The fluorine source comprises at least one of sodium fluoride, ammonium fluoride, potassium fluoride and lithium fluoride, and optionally comprises sodium fluoride;
[0030] (3) The vanadium source includes vanadium pentoxide and / or ammonium metavanadate;
[0031] (4) The phosphorus source includes at least one of diammonium phosphate, sodium phosphate, diammonium phosphate, monoammonium phosphate and triammonium phosphate.
[0032] In the technical solution of the embodiment of the present application, when sodium fluoride is used as the sodium source and / or the fluorine source, fluorine can be provided simultaneously with sodium, which is beneficial to reduce the input and waste of raw materials compared with the method of providing sodium and fluorine separately.
[0033] In some embodiments, the method for preparing the mixed slurry comprises:
[0034] The sodium source, the fluorine source, the vanadium source, and the phosphorus source are taken according to the stoichiometric ratio of Na3V2(PO4)2F3, and mixed with a solvent and the carbon source to form a first slurry;
[0035] After adjusting the pH of the first slurry to 6-7 by using a pH adjusting agent, grinding the slurry to obtain the mixed slurry;
[0036] Optionally, the pH adjuster includes at least one of aqueous ammonia, sodium hydroxide, sodium carbonate, sodium bicarbonate and ammonium bicarbonate, and further optionally includes aqueous ammonia.
[0037] In the technical solution of the embodiment of the present application, by using a pH regulator to adjust the pH of the first slurry to 6-7, the F in the mixed slurry can be effectively inhibited. - The hydrolysis of Na3V2(PO4)2F3 can be effectively inhibited, thereby inhibiting the formation of HF, effectively reducing the loss of F, and reducing the formation of impurities such as sodium vanadium phosphate in the finished product, so that the purity (content) of Na3V2(PO4)2F3 is effectively improved, thereby improving the capacity of the prepared positive electrode material.
[0038] In some embodiments, the mixed slurry further comprises a fluorine replenishing agent;
[0039] Optionally, the fluoride replenishing agent includes ammonium fluoride and / or sodium fluoride, and further optionally includes ammonium fluoride;
[0040] Optionally, the molar amount of the fluorine replenishing agent is 1% to 5% of the molar amount of the fluorine source.
[0041] In the technical solution of the embodiment of the present application, when the mixed slurry contains a fluorine replenisher, the fluorine replenisher can replenish this part of the F loss, effectively reduce the formation of impurities such as sodium vanadium phosphate in the finished product, and effectively improve the purity (content) of Na3V2(PO4)2F3, thereby improving the capacity of the prepared positive electrode material.
[0042] In some embodiments, the calcination temperature is 550°C to 800°C, preferably 650°C to 800°C; the calcination holding time is 3h to 10h, preferably 4h to 9h; the calcination is carried out in a protective atmosphere;
[0043] Optionally, the protective atmosphere includes nitrogen and / or argon.
[0044] In the technical scheme of the embodiment of the present application, the temperature or holding time of the calcining treatment is within the above respective ranges, which can improve the density of the carbon-containing coating layer while also improving the purity of Na3V2(PO4)2F3 in the positive electrode material. If the temperature of the calcining treatment is relatively low, or the holding time is relatively short, it is easy to cause incomplete carbonization of the carbon source forming the carbon-containing coating layer, and the degree of graphitization is low, so that the prepared positive electrode material has poor electronic conductivity and low capacity. In addition, when the temperature of the calcining treatment is relatively low, the carbon-containing coating layer formed is relatively loose, so that the compaction density of the positive electrode material is relatively low. If the sintering temperature is relatively high, or the holding time is relatively long, it is easy to cause more F loss, and the purity of the Na3V2(PO4)2F3 phase in the positive electrode material is low, resulting in a decrease in the capacity of the positive electrode material.
[0045] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising the positive electrode material described in the first aspect of the present application or the positive electrode material prepared by the preparation method described in the second aspect of the present application.
[0046] In this embodiment, the positive electrode plate contains the above-mentioned positive electrode material, and thus has a higher capacity and energy density.
[0047] In a fourth aspect, an embodiment of the present application provides a sodium ion battery, comprising the positive electrode sheet of the third aspect of the present application.
[0048] In this embodiment, the sodium ion battery includes the above-mentioned positive electrode plate, and thus has a higher capacity and energy density.
[0049] In a fifth aspect, an embodiment of the present application provides an electrical device comprising the sodium ion battery of the fourth aspect of the present application.
[0050] The electrical device of the present application includes the sodium ion battery provided by the present application, and thus has at least the same advantages as the sodium ion battery.
[0051] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0053] Figure 1 Schematic diagram of the preparation process flow of the positive electrode material provided in this application.
[0054] Figure 2 This is a morphology diagram of the positive electrode material prepared in Example 8 of the present application.
[0055] Figure 3 This is a morphology diagram of the positive electrode material prepared in Example 13 of the present application.
[0056] Figure 4 This is a morphology diagram of the positive electrode material prepared in Example 13 of the present application.
[0057] Figure 5 This is the first charge-discharge curve of the button cell made of the positive electrode material of Example 6 of the present application.
[0058] Figure 6 This is the first charge-discharge curve of the button cell made of the positive electrode material of Comparative Example 3 of the present application. DETAILED DESCRIPTION
[0059] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0060] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0061] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0062] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0063] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0064] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0065] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.
[0066] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.
[0067] At present, the NVPF materials that have been prepared usually have three voltage platforms in their discharge curves (relative to Na + / Na, about 4.1V, 3.6V and 3.3V~3.4V, but in theory, NVPF material has only two platforms (relative to Na + / Na is about 4.1V and 3.6V), among which the existence of the 3.3V~3.4V low-voltage platform will reduce the average discharge voltage and discharge specific capacity of the positive electrode material and the sodium ion battery using the material, thereby leading to a decrease in the battery energy density.
[0068] Based on the above phenomenon, the inventors discovered through research that the reason why the currently prepared NVPF materials have a low-voltage platform of 3.3V~3.4V is that when preparing NVPF materials, a solid-phase method is usually used. This method is prone to cause a lot of F loss during the preparation process, resulting in the presence of impurities such as sodium vanadium phosphate (Na3V2(PO4)3) in the finished product, thereby reducing the purity (content) of Na3V2(PO4)2F3 in the material, resulting in a low-voltage platform of 3.3V~3.4V, resulting in a lower product capacity and a low energy density of the sodium ion battery.
[0069] In order to solve the technical problems of poor capacity and poor electronic conductivity of current NVPF materials, the present application provides a positive electrode material and a preparation method thereof, a positive electrode plate, a sodium ion battery and an electrical device. Among them, by improving the current NVPF material and its preparation method, the technical effect of improving its electronic conductivity and capacity can be achieved, and then the capacity and energy density of the positive electrode plate, secondary battery and electrical device can also be improved.
[0070] In the first aspect, the present application provides a positive electrode material, which includes a core and a carbon-containing coating layer covered on at least a portion of the surface of the core, the core containing sodium vanadium fluorophosphate (Na3V2(PO4)2F3); a button battery is made of the positive electrode material, and the button battery is subjected to an Nth charge-discharge test. In the discharge curve of the Nth charge-discharge test, the discharge specific capacity is C0, and the total discharge specific capacity of the discharge platform corresponding to the voltage of 3.3V to 3.4V is C1, C1 / C0<6.7%, wherein N is an integer greater than or equal to 1; the conditions of the Nth charge-discharge test are: at 20°C to 30°C, the button battery is charged to 4.3V at a constant current of 0.2C, and then discharged to 2V at a constant current of 0.2C.
[0071] In some embodiments, the preparation process of the button cell is as follows: the positive electrode material, conductive agent, and binder provided in the present application are mixed in a certain mass ratio, and an appropriate amount of solvent is added to form a uniform electrode slurry, and then the electrode slurry is evenly coated on an aluminum foil, vacuum dried and cut into circular electrode sheets of a certain diameter, and then transferred to a glove box for standby use. Sodium metal is used as a counter electrode, glass fiber is used as a diaphragm, and an electrolyte is added to assemble a button cell. The entire assembly process is carried out in a glove box filled with argon.
[0072] In some embodiments, the conductive agent includes one or more of carbon black, acetylene black, Ketjen black, and carbon nanotubes.
[0073] In some embodiments, the binder includes polyvinylidene fluoride (PVDF).
[0074] In some embodiments, in the electrode slurry, the mass ratio of the positive electrode material, the conductive agent, and the binder is (80:10:10) to (90:5:5).
[0075] In some embodiments, the solvent in the electrode slurry includes at least one of N-methylpyrrolidone (NMP) and water.
[0076] In some embodiments, the diameter of the circular electrode sheet is 15 mm to 20 mm.
[0077] In some embodiments, the electrolyte comprises an electrolyte, an organic solvent and optional additives, the electrolyte comprising at least one of sodium perchlorate (NaClO4) and sodium hexafluorophosphate (NaPF6), the organic solvent comprising one or more of propylene carbonate, ethylene carbonate and dimethyl carbonate, and the additive comprising fluoroethylene carbonate.
[0078] In some embodiments, the concentration of the electrolyte contained in the electrolyte is 1 mol / L to 1.5 mol / L. As an example, the preparation process of the button cell described in the present application is as follows: the positive electrode material, conductive carbon black and polyvinylidene fluoride (PVDF) provided in the present application are mixed in a mass ratio of 85:8:7, and an appropriate amount of N-methylpyrrolidone (NMP) is added to form a uniform electrode slurry, and then the electrode slurry is evenly coated on aluminum foil, vacuum dried and cut into a circular electrode sheet with a diameter of 15 mm, and then transferred to a glove box for standby use. Sodium metal is used as the counter electrode, glass fiber is used as the diaphragm, the solute of the electrolyte is sodium perchlorate, the solvent of the electrolyte is propylene carbonate, ethylene carbonate and fluoroethylene carbonate (volume ratio of 1:1:0.05), the concentration of sodium perchlorate in the electrolyte is 1 mol / L, and a CR2032 button cell is assembled, and the entire assembly process is carried out in a glove box filled with argon.
[0079] It should be noted that the aforementioned discharge curve usually uses specific capacity (in mAh / g) as the horizontal axis and voltage (in V) as the vertical axis. In the discharge curve, in the interval of 3.3V to 3.4V of the vertical axis voltage, there is a discharge platform that is approximately parallel to the horizontal axis. Assuming that the specific capacities corresponding to the two endpoints of the discharge platform are C1' and C2' respectively, C1=|C1'-C2'|, that is, the absolute value of the difference between C1' and C2'; and C0 is the intersection value of the end of the discharge curve and the horizontal axis, that is, the specific capacity corresponding to the voltage of 0.
[0080] In some embodiments, N can be an integer of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 30, 40, 50, 60, 70, 80, 90, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, etc.
[0081] In some embodiments, C1 / C0 can be 0, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 6.7% or a range thereof.
[0082] The above-mentioned positive electrode material provided in the present application contains Na3V2(PO4)2F3 and optional Na3V2(PO4)3. After the positive electrode material is made into a button battery, when the positive electrode material contains Na3V2(PO4)3, in the Nth discharge curve, there is a discharge platform in the voltage range of 3.3V to 3.4V, and the discharge platform corresponds to the discharge process of Na3V2(PO4)3. The ratio of the discharge specific capacity corresponding to the discharge platform to the Nth discharge specific capacity C1 / C0 can reflect the mass proportion of Na3V2(PO4)3 impurity phase in the positive electrode material; and the lower C1 / C0 is, the lower the mass proportion of Na3V2(PO4)3 impurity phase in the positive electrode material is.
[0083] The present application makes C1 / C0 < 6.7%, indicating that the purity of Na3V2(PO4)2F3 in the core of the positive electrode material is relatively high, while the mass proportion of impurities such as Na3V2(PO4)3 is relatively low, which is conducive to effectively improving the capacity of the positive electrode material and the energy density of the sodium ion battery. At the same time, the carbon-containing coating layer in the positive electrode material can effectively improve the electronic conductivity of NVPF, so that the capacity of the material can be further improved.
[0084] In some embodiments, C1 / C0≤3.5%. For example, C1 / C0 can be 0, 0.1%, 0.3%, 0.7%, 0.9%, 1.1%, 1.3%, 1.7%, 2.1%, 2.3%, 2.7%, 3.1%, 3.3%, 3.5% or any range thereof.
[0085] In the technical solution of the embodiment of the present application, C1 / C0 is controlled to be within the above range, that is, the mass proportion of Na3V2(PO4)3 impurity phase in the positive electrode material is controlled to be lower, and correspondingly, Na3V2(PO4)2F3 has a higher mass proportion in the positive electrode material, that is, the purity of NVPF phase in the positive electrode material is made higher, which is beneficial to further effectively improve the capacity of the positive electrode material and the energy density of the sodium ion battery.
[0086] In some embodiments, the coverage rate of the surface of the core coated by the carbon-containing coating layer is 89% to 100%, preferably 95% to 100%, which is beneficial to the improvement of the capacity and corrosion resistance of the positive electrode material, and can make the positive electrode material have good electronic conductivity. For example, the coverage rate of the surface of the core coated by the carbon-containing coating layer in the positive electrode material can be 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100% or within the range of any of the above numbers.
[0087] It can be understood that the "coverage rate" mentioned in the present application refers to the ratio of the area of the inner core surface covered by the carbon-containing coating layer to the inner core surface area.
[0088] In some embodiments, the mass fraction of carbon in the positive electrode material is 1.25% to 6%, preferably 1.5% to 3.5%. For example, the mass fraction of carbon in the positive electrode material can be 1.25%, 1.5%, 1.7%, 1.9%, 2.1%, 2.3%, 2.5%, 2.7%, 2.9%, 3.1%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, 4.7%, 5%, 5.3%, 5.5%, 5.7%, 6% or within the range of any of the above values.
[0089] It can be understood that the mass fraction of the carbon element in the positive electrode material refers to the mass percentage of the carbon element in the positive electrode material.
[0090] In the technical solution of the embodiment of the present application, the mass fraction of the carbon element in the positive electrode material is within the above range, which is conducive to taking into account both the compaction density and the electronic conductivity. If the mass fraction of the carbon element in the positive electrode material is relatively high, it is easy to form too many loose porous carbon layers on the surface of the positive electrode material, resulting in a decrease in the compaction density. If the mass fraction of the carbon element in the positive electrode material is relatively low, the electronic conductivity is poor and the material capacity is low.
[0091] In some embodiments, the porosity of the positive electrode material is 10% to 69%, preferably 15% to 30%. For example, the porosity can be 10%, 15%, 17%, 19%, 21%, 23%, 25%, 27%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 69% or within the range of any of the above values. The above porosity is conducive to ensuring the entry and exit of sodium ions while making the carbon-containing coating layer more compact, which is conducive to improving the compaction density of the positive electrode material.
[0092] In some embodiments, the compaction density of the positive electrode material is 1.4 g / cm 3 ~2g / cm 3 , preferably 1.53 g / cm 3 ~1.99g / cm 3 For example, the compacted density may be 1.4 g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2g / cm 3 Or within a range consisting of any of the above values.
[0093] It should be noted that the compaction density of the positive electrode material refers to the compaction density of the positive electrode material under a pressure of 30 kN.
[0094] In the technical solution of the embodiment of the present application, the positive electrode material has a higher compaction density, so that the sodium ion battery can have a higher energy density.
[0095] In a second aspect, the present application provides a method for preparing a positive electrode material, which can be used to prepare the positive electrode material of the first aspect of the present application, and may include the following steps S1 to S3:
[0096] S1: providing a mixed slurry, wherein the mixed slurry comprises a sodium source, a fluorine source, a vanadium source, a phosphorus source and a carbon source;
[0097] S2: The mixed slurry is dried to obtain a precursor;
[0098] S3: The precursor is calcined to obtain the positive electrode material; wherein the positive electrode material includes a core and a carbon-containing coating layer covering at least a portion of the surface of the core, and the core contains sodium vanadium fluorophosphate (Na3V2(PO4)2F3); a button battery is made of the positive electrode material, and the button battery is subjected to an Nth charge-discharge test, in the Nth discharge curve, the discharge specific capacity is C0, and the total discharge specific capacity of the discharge platform corresponding to the voltage of 3.3V to 3.4V is C1, C1 / C0<6.7%, wherein N is an integer greater than or equal to 1; the conditions of the Nth charge-discharge test are: at 20℃~30℃, the button battery is charged to 4.3V at a constant current of 0.2C, and then discharged to 2V at a constant current of 0.2C.
[0099] The inner core of the positive electrode material obtained by the above-mentioned preparation method provided by the present application has a high purity of Na3V2(PO4)2F3, while the mass proportion of impurities such as Na3V2(PO4)3 is low, which effectively improves the capacity of the positive electrode material and the energy density of the sodium ion battery. At the same time, the carbon-containing coating layer in the positive electrode material obtained by the above-mentioned preparation method can effectively improve the electronic conductivity of the positive electrode material, so that the capacity of the material can be further improved.
[0100] In some embodiments, the carbon source comprises at least one of citric acid, polyvinyl alcohol, glucose, sucrose and oxalic acid; optionally comprising citric acid and / or polyvinyl alcohol (PEG).
[0101] In the technical solution of the embodiment of the present application, when the carbon source includes citric acid, the mixed slurry includes a vanadium source. In this case, the citric acid can be used as a reducing agent to reduce the valence of vanadium and complex V 4+ and / or V 5+ , increasing the solubility of vanadium in the mixed slurry, thereby achieving ion-level mixing of multiple elements. This can make the element distribution in the precursor obtained after drying more uniform, facilitate the migration and fusion of ions during calcination, and thus help to improve the purity of the Na3V2(PO4)2F3 phase in the product.
[0102] In the technical solution of the embodiment of the present application, when the carbon source includes polyvinyl alcohol, since the carbon-containing coating layer formed after sintering of polyvinyl alcohol is denser, it helps to increase the compaction density of the positive electrode material, thereby facilitating improving the energy density of the sodium ion battery.
[0103] In some embodiments, the carbon source comprises citric acid and polyvinyl alcohol.
[0104] In the technical solution of the embodiment of the present application, when the carbon source includes citric acid and polyvinyl alcohol, the compounding of citric acid and polyvinyl alcohol can produce a mutually promoting effect, thereby achieving a further improvement in the compaction density, which is beneficial to improving the energy density of the sodium ion battery using the positive electrode material.
[0105] In some embodiments, when the carbon source is citric acid and polyvinyl alcohol, the mass ratio of the citric acid to the polyvinyl alcohol is 2:1 to 1:4, preferably 2:1 to 1:3. For example, the mass ratio of citric acid to polyvinyl alcohol can be 2:1, 1:1, 1:2, 1:3, 1:4 or within the range of any of the above values, which is conducive to further improving the compaction density of the positive electrode material.
[0106] In some embodiments, the polyvinyl alcohol includes at least one of polyvinyl alcohol 2000, polyvinyl alcohol 3000, polyvinyl alcohol 4000, and polyvinyl alcohol 6000.
[0107] It should be noted that the "polyvinyl alcohol 2000" mentioned in the present application refers to polyvinyl alcohol having a weight average molecular weight of 2000; other polyvinyl alcohols are similar, all referring to polyvinyl alcohols having a weight average molecular weight of 3000, 4000 or 6000 respectively.
[0108] In some embodiments, the sodium source includes at least one of sodium fluoride, sodium phosphate, sodium bicarbonate, and sodium nitrate, and optionally includes sodium fluoride.
[0109] In some embodiments, the fluoride source includes at least one of sodium fluoride, ammonium fluoride, potassium fluoride, and lithium fluoride, and optionally includes sodium fluoride.
[0110] In the technical solution of the embodiment of the present application, when sodium fluoride is used as the sodium source and / or the fluorine source, fluorine can be provided simultaneously with sodium, which is beneficial to reduce the input and waste of raw materials compared with the method of providing sodium and fluorine separately.
[0111] In some embodiments, the vanadium source includes vanadium pentoxide and / or ammonium metavanadate.
[0112] In some embodiments, the phosphorus source includes at least one of diammonium phosphate, sodium phosphate, diammonium phosphate, monoammonium phosphate, and triammonium phosphate.
[0113] In some embodiments, the method for preparing the mixed slurry may include the following steps:
[0114] Step S10: taking the sodium source, the fluorine source, the vanadium source, and the phosphorus source according to the stoichiometric ratio of Na3V2(PO4)2F3, and mixing them with a solvent and the carbon source to form a first slurry;
[0115] Step S20: After adjusting the pH value of the first slurry to 6-7 using a pH adjuster, grinding the slurry to obtain the mixed slurry.
[0116] In the technical solution of the embodiment of the present application, the mixed slurry is ground to reduce the particle size of the mixed slurry and increase the solubility of various raw materials, thereby facilitating ionic mixing of multiple elements, making the element distribution in the resulting precursor more uniform, and facilitating the migration and fusion of ions during calcination, thereby helping to improve the purity of the Na3V2(PO4)2F3 phase in the product.
[0117] In some embodiments, the drying process is spray drying.
[0118] The inventors found during the research that the mixed slurry contains a fluorine source, and the F in the fluorine source - It will partially hydrolyze to generate HF, which can easily cause corrosion to the spray drying equipment. More importantly, HF will partially volatilize during the spray drying process, which will lead to F loss, making it easy to generate more impurities such as sodium vanadium phosphate in the finished product, and reduce the purity (content) of Na3V2(PO4)2F3, thus resulting in a 3.3V low-voltage platform, resulting in a lower product capacity.
[0119] The preparation method provided in the present application can effectively inhibit the F in the mixed slurry by adjusting the pH value of the mixed slurry to 6-7. - The hydrolysis of Na3V2(PO4)2F3 can be inhibited and the generation of HF can be suppressed, which can effectively reduce the loss of F and the generation of impurities such as sodium vanadium phosphate in the finished product, so that the purity (content) of Na3V2(PO4)2F3 can be effectively improved, thereby improving the capacity of the prepared positive electrode material.
[0120] It can be understood that the "purity of Na3V2(PO4)2F3 (phase)" mentioned in this application refers to the mass percentage of Na3V2(PO4)2F3 in the positive electrode material.
[0121] In some embodiments, the pH of the mixed slurry can be 6, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7 or a range thereof.
[0122] In some embodiments, the pH adjuster includes at least one of aqueous ammonia, sodium hydroxide, sodium carbonate, sodium bicarbonate, and ammonium bicarbonate, and optionally includes aqueous ammonia.
[0123] In the technical solution of the embodiment of the present application, when ammonia water is used as the pH regulator, the ammonia water can easily volatilize by generating ammonia gas during the subsequent calcination process, so other impurity elements will not be introduced, and the purity of Na3V2(PO4)2F3 in the prepared positive electrode material can be improved.
[0124] In some embodiments, the type of the solvent is not limited, and water commonly used in the art can be used as the solvent; for example, at least one of pure water, deionized water, or distilled water.
[0125] In some embodiments, the mixed slurry further includes a fluorine replenishing agent.
[0126] In the process of calcining the precursor in the aforementioned step S3, there is usually a partial loss of F. When the mixed slurry contains a fluorine replenishing agent, the fluorine replenishing agent can replenish this part of the F loss, effectively reduce the formation of impurities such as sodium vanadium phosphate in the finished product, and effectively improve the purity (content) of Na3V2(PO4)2F3, thereby improving the capacity of the prepared positive electrode material.
[0127] In some embodiments, the fluoride replenishing agent includes ammonium fluoride and / or sodium fluoride, and further includes ammonium fluoride.
[0128] In the technical solution of the embodiment of the present application, when ammonium fluoride is used as a fluorine supplement, on the one hand, F - On the other hand, during the subsequent calcination process, ammonium ions can evaporate in the form of ammonia gas, so no other impurity elements will be introduced, which can improve the purity of Na3V2(PO4)2F3 in the prepared positive electrode material.
[0129] In some embodiments, the molar amount of the fluorine replenishing agent is 1% to 5% of the molar amount of the fluorine source, preferably 3% to 5%. For example, the molar amount of the fluorine replenishing agent can be 1%, 1.5%, 2%, 2.5%, 3%, 3.1%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.1%, 4.3%, 4.5%, 4.7%, 5% of the molar amount of the fluorine source, or within the range of any of the above values, in order to effectively replenish the fluorine source. - At the same time, it can also avoid the adverse effects of excessive impurities and poor electrochemical performance in the finished product due to the relatively large molar amount of the fluorine replenisher.
[0130] In some embodiments, the calcination temperature is 550° C. to 800° C., preferably 650° C. to 800° C. For example, the calcination temperature can be 550° C., 600° C., 650° C., 660° C., 670° C., 680° C., 690° C., 700° C., 710° C., 720° C., 730° C., 740° C., 750° C., 800° C. or within a range consisting of any of the above values.
[0131] In some embodiments, the holding time of the calcination treatment is 3 h to 10 h, preferably 4 h to 9 h. For example, the holding time of the calcination treatment can be 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h or within the range of any of the above values.
[0132] It can be understood that the holding time of the calcination treatment refers to the time of holding the treatment at the temperature after the temperature is raised to the calcination treatment temperature.
[0133] In the technical scheme of the embodiment of the present application, the temperature or holding time of the calcining treatment is within the above respective ranges, which can improve the density of the carbon-containing coating layer while improving the purity of Na3V2(PO4)2F3 in the positive electrode material. If the temperature of the calcining treatment is relatively low, or the holding time is relatively short, it is easy to cause incomplete carbonization of the carbon source forming the carbon-containing coating layer, and the degree of graphitization is low, so that the prepared positive electrode material has poor electronic conductivity and low capacity. In addition, when the temperature of the calcining treatment is relatively low, the carbon-containing coating layer formed is relatively loose, which will make the compaction density of the positive electrode material lower. If the sintering temperature is relatively high, or the holding time is relatively long, it is easy to cause more F loss, and the purity of the Na3V2(PO4)2F3 phase in the positive electrode material is low, resulting in a decrease in the capacity of the positive electrode material.
[0134] In some embodiments, the temperature is raised to the calcination temperature, and the corresponding temperature raising process includes the following stages:
[0135] Stage 1: Raise the temperature from room temperature to 120℃~150℃, and keep it at 120℃~150℃ for 2~4h to consume the precursor as much as possible, and avoid excessive moisture content in the higher temperature stage, which consumes more carbon source;
[0136] Stage 2: Heating from 120℃~150℃ to 400℃~550℃, and keeping at 400℃~550℃ for 1~3h. This stage can promote the decomposition of organic matter in the precursor and the reduction of vanadium;
[0137] Stage 3: Raise the temperature from 400℃~550℃ to 550℃~800℃, and keep at 550℃~800℃ for 5~9h.
[0138] It should be noted that the room temperature mentioned in this application refers to 25°C to 35°C.
[0139] In some embodiments, in stage 1, the insulation temperature can be 120°C, 130°C, 140°C, 150°C or within the range of any of the above values, and the insulation time can be 2h, 3h, 4h or within the range of any of the above values.
[0140] In some embodiments, in stage 2, the insulation temperature can be 400°C, 450°C, 500°C, 550°C or within the range of any of the above values, and the insulation time can be 1h, 2h, 3h or within the range of any of the above values.
[0141] In some embodiments, in stage 3, the holding temperature may be 550°C, 600°C, 650°C, 700°C, 750°C, 800°C or any range thereof, and the holding time may be 5h, 6h, 7h, 8h, 9h or any range thereof.
[0142] In some embodiments, the calcination process is performed in a protective atmosphere. Optionally, the protective atmosphere includes nitrogen and / or argon.
[0143] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising the positive electrode material of the first aspect of the present application or the positive electrode material prepared by the preparation method of the second aspect of the present application.
[0144] The positive electrode plate contains the positive electrode material of the first aspect of the present application or the positive electrode material prepared by the preparation method of the second aspect of the present application, and thus has a higher capacity and energy density.
[0145] In a fourth aspect, an embodiment of the present application provides a sodium ion battery, comprising the positive electrode sheet of the third aspect of the present application.
[0146] The sodium ion battery includes the positive electrode plate of the third aspect of the present application, and thus has a higher capacity and energy density.
[0147] In a fifth aspect, an embodiment of the present application provides an electrical device, comprising the sodium ion battery of the fourth aspect of the present application.
[0148] The electrical device includes the sodium ion battery of the fourth aspect of the present application, and thus has at least the same advantages as the sodium ion battery.
[0149] In some embodiments, the electric device may be, but is not limited to, a mobile phone, a tablet, a laptop, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, etc. Among them, the electric toy may include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc., and the spacecraft may include an airplane, a rocket, a space shuttle, and a spacecraft, etc.
[0150] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0151] 1. Preparation method
[0152] Example 1
[0153] (1) Sodium fluoride (257.07 g), vanadium pentoxide (365.59 g) and ammonium dihydrogen phosphate (464.28 g) were dispersed in water according to the stoichiometric ratio of Na3V2(PO4)2F3, and citric acid and polyvinyl alcohol (the mass ratio of the two was 2:1, and the weight average molecular weight of polyvinyl alcohol was 2000, wherein the total mass ratio = the total mass of citric acid and polyvinyl alcohol / the total mass of sodium fluoride, vanadium pentoxide, ammonium dihydrogen phosphate, citric acid and polyvinyl alcohol) were added as carbon sources to form a first slurry; ammonia water was added to the first slurry to adjust the pH value to 6; and then the slurry was put into a sand mill for cyclic grinding at a grinding speed of 1000 r / min for 3 hours to obtain a mixed slurry.
[0154] (2) The mixed slurry is spray-dried to obtain a precursor.
[0155] (3) The precursor is transferred into a sintering kiln and calcined in an argon protective atmosphere, and the oxygen content in the sintering kiln is controlled to be ≤10ppm, the moisture content in the highest temperature insulation section is ≤10ppm, the CO content is ≤10ppm, and the H2 content is ≤10ppm; the temperature rising process in the sintering kiln is as follows: from room temperature to 140°C, and kept at 140°C for 3h; from 140°C to 500°C, and kept at 500°C for 2h; from 500°C to 705°C, the calcination temperature is maintained at 705°C, and kept at this temperature for 6.5h to obtain the positive electrode material.
[0156] Example 2
[0157] The preparation process is similar to that of Example 1, with the main difference being that in step (1), the pH value is adjusted to 7.
[0158] Embodiments 3 to 7
[0159] The preparation process is similar to that of Example 1, with the main difference being that ammonium fluoride is added to the mixed solution in step (1) as a fluorine replenishing agent, and the molar amount of ammonium fluoride is respectively equivalent to 1%, 2%, 3%, 5% and 8% of the molar amount of sodium fluoride.
[0160] Embodiments 8 to 11
[0161] The preparation process is similar to that of Example 1, with the main difference being that in step (1), the mass ratios of citric acid to polyvinyl alcohol are 1:1, 1:2, 1:3, and 1:4, respectively.
[0162] Example 12
[0163] The preparation process is similar to that of Example 1, with the main difference being that in step (1), an equal amount of citric acid is used instead of polyvinyl alcohol.
[0164] Embodiment 13
[0165] The preparation process is similar to that of Example 1, with the main difference being that in step (1), an equal amount of polyvinyl alcohol is used instead of citric acid.
[0166] Embodiment 14
[0167] The preparation process is similar to that of Example 1, with the main difference being that in step (1), equal amounts of glucose are used to replace polyvinyl alcohol and citric acid.
[0168] Examples 15 to 21
[0169] The preparation process is similar to that of Example 1, with the main difference being that in step (1), the total mass proportion of citric acid and polyvinyl alcohol is adjusted so that the mass fraction of carbon element in the prepared positive electrode material is 1.25%, 1.5%, 2%, 2.3%, 3%, 5%, and 6%, respectively, and the corresponding total masses of citric acid and polyvinyl alcohol are 152.17 g, 182.61 g, 243.48 g, 280 g, 365.22 g, 608.70 g, and 730.43 g, respectively.
[0170] Examples 22 to 27
[0171] The preparation process is similar to that of Example 1, with the main difference being that in step (3), the calcination temperatures are 500°C, 600°C, 650°C, 750°C, 700°C, and 800°C, respectively.
[0172] Embodiments 28 to 35
[0173] The preparation process is similar to that of Example 1, with the main difference being that in step (3), the holding time for the calcination treatment is 3h, 4h, 5h, 6h, 7h, 8h, 9h, and 10h, respectively.
[0174] Embodiments 36 to 37
[0175] The preparation process is similar to that of Example 1, with the main difference being that in step (1), the weight average molecular weights of the polyvinyl alcohol are 6000 and 4000 respectively.
[0176] Comparative Examples 1-2
[0177] The preparation process is similar to that of Example 1, with the main difference being that in step (1), the pH is adjusted to 4 and 5 respectively.
[0178] Comparative Example 3
[0179] The preparation process is similar to that of Example 1, with the main difference being that in step (1), the pH value is adjusted to 8.
[0180] 2. Test Method
[0181] 1. The mass fraction of carbon in the positive electrode material can be tested by the following method: refer to YS / T 1028.4-2015 Chemical Analysis Method for Lithium Iron Phosphate Part 4 "Determination of Carbon Content" and use high-frequency combustion infrared absorption method for testing.
[0182] 2. The compaction density of the positive electrode material is tested using a compaction density meter with a test pressure of 3 tons (T) and a pressing time of 30S.
[0183] 3. The porosity test of the positive electrode material refers to TCSTM 00553-2022 Porosity Determination Method for Lightweight Porous Materials.
[0184] 4. The coverage of the carbon-containing coating layer was measured using a transmission electron microscope (TEM) and an energy dispersive X-ray spectrometer (EDX).
[0185] 5. Properties test of sodium ion batteries
[0186] (1) Preparation of button cells:
[0187] Preparation of positive electrode sheet: The positive electrode material prepared in the above embodiment or comparative example, the binder sodium alginate and the conductive agent acetylene black are dispersed and dissolved in N-methylpyrrolidone (NMP) solvent at a mass ratio of 8:1:1 to obtain positive electrode slurry. The positive electrode slurry is coated on both sides of the aluminum foil current collector, and after drying, cold pressing and slitting, the positive electrode sheet is obtained.
[0188] Battery assembly: Sodium metal was used as the counter electrode, glass fiber was used as the separator, the electrolyte solute was sodium perchlorate, the electrolyte solvent was propylene carbonate, ethylene carbonate and fluoroethylene carbonate (volume ratio of 1:1:0.05), the concentration of sodium perchlorate in the electrolyte was 1 mol / L, and CR2032 button cells were assembled. The entire assembly process was carried out in a glove box filled with argon. The button cells were left to stand for 6 hours before being used for subsequent electrochemical performance tests.
[0189] (2) First charge specific capacity and first discharge specific capacity test
[0190] The test was conducted on a Blue Battery Tester (CT2001A). At 20℃~30℃ and normal pressure, the button cell was charged to 4.3V at a constant rate of 0.2C, and then discharged to 2V at a constant rate of 0.2C. The humidity of the test environment was less than 15%. The charge-discharge mode was cycled for 500 cycles, and the discharge specific capacity and capacity retention rate after 500 cycles were measured.
[0191] First cycle coulombic efficiency = first discharge specific capacity / first charge specific capacity × 100%
[0192] Table 1
[0193]
[0194]
[0195] Table 2
[0196]
[0197]
[0198] III. Analysis of test results of various embodiments and comparative examples
[0199] Figures 2 to 4 It shows that the positive electrode material prepared in the present application has a core-shell morphology and a relatively uniform particle size distribution.
[0200] Figure 5 In the discharge curve, there is almost no voltage platform in the voltage range of 3.3V~3.4V, indicating that the content of Na3V2(PO4)3 impurity phase in the positive electrode material is extremely low. Figure 6 In the discharge curve, the discharge specific capacity of the discharge platform corresponding to 3.3V~3.4V is (98-89) mAh / g, and the first discharge specific capacity is 111 mAh / g. Correspondingly, in Comparative Example 3, C1 / C0=8.1%, and the Na3V2(PO4)3 impurity content is relatively high.
[0201] As shown in Table 1, in the positive electrode materials prepared in each embodiment, the mass fraction of carbon element is between 1.25% and 6%, the coverage rate of the carbon-containing coating layer is between 89% and 100%, the porosity of the positive electrode material is between 10% and 69%, and the compaction density is 1.4 g / cm 3 ~2g / cm 3 and C1 / C0 is less than 6.7%, further, C1 / C0 is less than or equal to 6.1%; while the positive electrode materials prepared in Comparative Examples 1 to 3 have C1 / C0 greater than or equal to 6.7%.
[0202] Furthermore, in each embodiment, since ammonia water is added to the first slurry and the pH is adjusted to 6-7, the F in the slurry can be effectively inhibited. - The hydrolysis of F can be inhibited and the generation of HF can be inhibited, so the loss of F can be effectively reduced and the generation of impurities such as sodium vanadium phosphate in the finished product can be reduced. Therefore, the mass proportion of Na3V2(PO4)3 impurity phase in the positive electrode material is relatively low, and the purity of NVPF phase is relatively high, and finally C1 / C0 is less than 6.7%. Combined with the first charge specific capacity, the first discharge specific capacity, the discharge specific capacity after 500 cycles and the capacity retention rate after 500 cycles in Table 2, it can be seen that the positive electrode material provided in the embodiment of the present application has a higher capacity and a higher capacity retention rate, and has a higher energy density. However, since the pH value of Comparative Examples 1 to 3 is less than 6 or greater than 7, it is difficult to suppress the generation of HF and the loss of F. Therefore, the mass proportion of the Na3V2(PO4)3 impurity phase in the positive electrode material is relatively high, and the purity of the NVPF phase is low, which is ultimately manifested as C1 / C0 being greater than or equal to 6.7%. Combined with the first charge specific capacity, first discharge specific capacity, discharge specific capacity after 500 cycles and capacity retention rate after 500 cycles in Table 2, it can be seen that the capacity and capacity retention rate of the positive electrode materials obtained in Comparative Examples 1 to 3 are low, and the energy density is low.
[0203] Further, in combination with the results of Example 1 and Example 3 to Example 7 in Table 1 and Table 2, it can be seen that, on the basis of Example 1, after adding an appropriate amount of ammonium fluoride as a fluorine replenisher, Examples 3 to 6 supplement the F loss, reduce the generation of impurities such as sodium vanadium phosphate in the finished product, and are beneficial to the purity of Na3V2(PO4)2F3. It is manifested as a C1 / C0 value equivalent to or smaller than that of Example 1, and then has a discharge specific capacity of 500 cycles equivalent to or higher than that of the embodiment; and Example 7 has a relatively large molar amount of ammonium fluoride added, resulting in too many impurities in the finished product, and then the discharge specific capacity of 500 cycles is lower than that of Example 1 and Example 3 to Example 6.
[0204] Combining the results of Example 1 and Example 12 in Table 1 and Table 2, it can be seen that compared with the single citric acid used as the carbon source in Example 12, the addition of polyvinyl alcohol in Example 1 can make the carbon-containing coating layer more compact and improve the compaction density. Combining the results of Example 1 and Example 13 in Table 1 and Table 2, it can be seen that compared with the single polyvinyl alcohol used as the carbon source in Example 13, the addition of sodium citrate in Example 1 can improve the purity of the NVPF phase to a certain extent, which is manifested in a lower C1 / C0 and an increase in the discharge specific capacity after 500 cycles. Combining the results of Example 1 and Example 14 in Table 1 and Table 2, it can be seen that compared with the use of glucose as the carbon source in Example 14, the use of citric acid and polyvinyl alcohol in Example 1 can improve the compaction density.
[0205] Combining the results of Example 1, Example 8 to Example 11 in Table 1 and Table 2, it can be seen that when the mass ratio of sodium citrate to polyvinyl alcohol is in the range of 2:1 to 1:3, the corresponding button battery has a better discharge capacity after 500 cycles. Combining the results of Example 1, Example 15 to Example 21 in Table 1 and Table 2, it can be seen that when the mass fraction of carbon in the positive electrode material is between 1.5% and 3.5%, the corresponding button battery has a better discharge capacity after 500 cycles. Combining the results of Example 1, Example 22 to Example 27, Example 28 to Example 35 in Table 1 and Table 2, it can be seen that the temperature and time of the calcination treatment will affect the purity of NVPF in the positive electrode material and the compaction density of the positive electrode material, thereby affecting the performance of the corresponding button battery. Specifically, when the calcination temperature is 650°C to 800°C and the calcination time is 5h to 9h, the corresponding button battery has a relatively higher discharge capacity after 500 cycles.
[0206] In summary, by making C1 / C0<6.7%, the positive electrode material and the battery using the positive electrode material can perform better in terms of capacity and capacity retention rate.
[0207] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A positive electrode material, characterized in that: The invention comprises an inner core and a carbon-containing coating layer covering at least a portion of the surface of the inner core, wherein the inner core comprises sodium vanadium fluorophosphate; A button battery is made of the positive electrode material, and the button battery is subjected to an Nth charge-discharge test. In the discharge curve of the Nth charge-discharge test, the discharge specific capacity is C0, the discharge specific capacity of the discharge platform corresponding to the voltage of 3.3V to 3.4V is C1, and C1 / C0<6.7%, wherein N is an integer greater than or equal to 1; The conditions of the Nth charge-discharge test are: at 20° C. to 30° C., the button battery is charged to 4.3V at a constant current of 0.2C, and then discharged to 2V at a constant current of 0.2C.
2. The positive electrode material according to claim 1, characterized in that Satisfy at least one of the following conditions: (1) C1 / C0≤3.5%; (2) The coverage rate of the carbon-containing coating layer on the surface of the inner core is 89% to 100%, preferably 95% to 100%; (3) The porosity of the positive electrode material is 10% to 69%, preferably 15% to 30%; (4) The mass fraction of carbon in the positive electrode material is 1.25% to 6%, preferably 1.5% to 3.5%; (5) The compaction density of the positive electrode material is 1.4 g / cm 3 ~2g / cm 3 , preferably 1.53 g / cm 3 ~1.99g / cm 3 .
3. A method for preparing a positive electrode material, characterized in that: include: Providing a mixed slurry, wherein the mixed slurry comprises a sodium source, a fluorine source, a vanadium source, a phosphorus source and a carbon source; The mixed slurry is dried to obtain a precursor; The precursor is calcined to obtain the positive electrode material; The positive electrode material comprises a core and a carbon-containing coating layer covering at least a portion of the surface of the core, wherein the core comprises sodium vanadium fluorophosphate; a button battery is made of the positive electrode material, and the button battery is subjected to an Nth charge-discharge test, in a discharge curve of the Nth charge-discharge test, the discharge specific capacity is C0, the discharge specific capacity of the discharge platform corresponding to the voltage of 3.3V to 3.4V is C1, C1 / C0<6.7%, wherein N is an integer greater than or equal to 1; the conditions of the Nth charge-discharge test are: at 20°C to 30°C, the button battery is charged to 4.3V at a constant current rate of 0.2C, and then discharged to 2V at a constant current rate of 0.2C.
4. The preparation method according to claim 3, characterized in that: The carbon source comprises at least one of citric acid, polyvinyl alcohol, glucose, sucrose and oxalic acid, optionally comprises citric acid and / or polyvinyl alcohol, and further optionally comprises citric acid and polyvinyl alcohol; Optionally, when the carbon source is citric acid and polyvinyl alcohol, the mass ratio of the citric acid to the polyvinyl alcohol is 2:1 to 1:4; Optionally, the polyvinyl alcohol includes at least one of polyvinyl alcohol 2000, polyvinyl alcohol 3000, polyvinyl alcohol 4000 and polyvinyl alcohol 6000.
5. The preparation method according to claim 3 or 4, characterized in that: The sodium source includes at least one of sodium fluoride, sodium phosphate, sodium bicarbonate and sodium nitrate, and optionally includes sodium fluoride; The fluorine source includes at least one of sodium fluoride, ammonium fluoride, potassium fluoride and lithium fluoride, and optionally includes sodium fluoride; The vanadium source includes vanadium pentoxide and / or ammonium metavanadate; The phosphorus source includes at least one of diammonium phosphate, sodium phosphate, diammonium phosphate, monoammonium phosphate and triammonium phosphate.
6. The preparation method according to claim 3 or 4, characterized in that: The preparation method of the mixed slurry comprises: The sodium source, the fluorine source, the vanadium source, and the phosphorus source are taken according to the stoichiometric ratio of sodium vanadium fluorophosphate, and mixed with a solvent and the carbon source to form a first slurry; After adjusting the pH value of the first slurry to 6-7 by using a pH adjusting agent, grinding the slurry to obtain the mixed slurry; Optionally, the pH adjuster includes at least one of aqueous ammonia, sodium hydroxide, sodium carbonate, sodium bicarbonate and ammonium bicarbonate, and further optionally includes aqueous ammonia.
7. The preparation method according to claim 3 or 4, characterized in that: The mixed slurry also contains a fluorine replenishing agent; Optionally, the fluoride replenishing agent includes ammonium fluoride and / or sodium fluoride, and further optionally includes ammonium fluoride; Optionally, the molar amount of the fluorine replenishing agent is 1% to 5% of the molar amount of the fluorine source.
8. The preparation method according to claim 3 or 4, characterized in that: The calcination temperature is 550°C to 800°C, preferably 650°C to 800°C; the calcination holding time is 3h to 10h, preferably 4h to 9h; the calcination is carried out in a protective atmosphere; Optionally, the protective atmosphere includes nitrogen and / or argon.
9. A positive electrode sheet, characterized in that: The positive electrode material comprises the positive electrode material according to claim 1 or 2 or the positive electrode material prepared by the preparation method according to any one of claims 3 to 8.
10. A sodium ion battery, characterized in that: Including the positive electrode sheet as described in claim 9.
Citation Information
Patent Citations
Composite cathode material of sodium-ion battery and preparation method of composite cathode material
CN105655565A
Method for controllably preparing vanadium sodium fluorophosphate positive electrode material
CN108682855A
Preparation method of sodium vanadium trifluorophosphate serving as positive electrode material of sodium-ion battery
CN111606314A
Sodium vanadium fluorophosphate-sodium vanadium phosphate composite material as well as preparation method and application thereof
CN117577829A
Preparation method and application of sodium vanadium fluorophosphate / C positive electrode material
CN118472224A
Cited By
Preparation method of positive electrode material, pole piece and battery
CN119864403A
Positive electrode sheet for sodium-ion battery, and battery, battery pack and electric device
WO2026158105A1